Odpowiedź :
Zad. 6 w zalaczniku
Zad. 7
[tex]a)\\4*(-0.2)*(-0.25)=4*0.05=0.2\\b) \\\frac12*(-\frac34)*8=\frac12*(-3)*2=-3\\c)\\(-8)*(-1\frac13)*\frac54*(-0.1)=(-8)*(-\frac43)*\frac54*(-0.1)=0.8*(-\frac53)=\frac8{10}*(-\frac53)=\frac82*(-\frac13)=-\frac86=-\frac43[/tex]
[tex]d) \\8*(-0.7)*(-\frac12)*10=8*(-\frac7{10})*(-\frac12)*10=(-4)*(-7)=28[/tex]
[tex]e)\\-5*\frac23*(-1.5)*0.2=-5*\frac23*(-\frac32)*\frac{1}{5}=(-1)*(-1)=1[/tex]
[tex]f)\\-\frac37*\frac56*(-4.9)*20=-\frac17*\frac52*(-\frac{49}{10})*20=-\frac17*\frac52*(-\frac{49}1)*2=-1*5*(-7)=-5*(-7)=35[/tex]
Zad. 8
[tex]\text{POZIOMO}\\A: -4*(-8)=32\\B: \frac{-480}{-10}=48\\E: (-15\frac12+(-\frac12))(-15\frac12-(-\frac12))=(-\frac{31}2-\frac12)(-\frac{31}2+\frac12)=-\frac{32}2*(-\frac{30}2)=-16*(-15)=240[/tex]
[tex]H: (-2)*(-16)+1=32+1=33\\I: \frac{1}{\frac{-3}{{-63}}}=\frac{1}{\frac1{12}}=1:\frac1{12}=1*12=12[/tex]
[tex]\text{PIONOWO:}\\A: (-8)*2-(-52)=-16+52=36\\C: -((-27)*3)=-(-81)=81\\D: 36:(-3)*(-7-5)=-12*(-12)=(-12)^2=144\\F: 2(16\frac12+(-5))=2(16\frac12-5)=2*11\frac12=2*\frac{23}2=23\\G: \text{ucielo liczbe :)}[/tex]